Generational perspectives and advocacy barriers among community health workers: implications for public health workforce leadership - Venus Gines; Joanna Rodriguez; Diana Lobaina; Lea Sacca; Mariarebecca Torres; Maria C. Mejia (Frontiers in Public Health)
Community Health Workers (CHWs) play a crucial role in the public health workforce, particularly within underserved communities where they enhance access to healthcare, address social determinants of health, and advocate for health-related policy changes. This Perspective examines how age and experience influence CHWs’ involvement in workforce diversity initiatives, advocacy activities, and job satisfaction. Using data from a cross-sectional survey conducted among 306 CHWs during statewide workforce development events in Texas, United States, we identified significant generational and experiential differences in CHW engagement. Younger CHWs (aged 20–30 years) were significantly more inclined to prioritize mentorship and role modeling (p = 0.011), while older CHWs (aged 61 years and above) favored policy-driven advocacy (p = 0.003). Limited funding was the most frequently reported barrier (48.4%), and CHWs with less than 1 year of experience reported higher levels of organizational barriers and discrimination. Job satisfaction notably increased with age, reaching 73% among CHWs aged 61 years and older. These insights underscore the need for tailored strategies to strengthen workforce retention, leadership cultivation, and systemic support for CHWs, ultimately enhancing public health infrastructure.